Upaya Meningkatkan Sopan Santun Mahasiswa dengan Mengimplementasikan Bimbingan Kelompok Berbasis Hadits - Jannati, Zhila; Hamandia, Muhammad Randicha; Razzaq, Abdur (Ghaidan: Jurnal Bimbingan Konseling Islam dan Kemasyarakatan, 2023)
The nobility of a person can be reflected in the presence of good manners in him. People who have high manners will be able to relate well to other people and can even become people who are really liked and missed by other people. This research on "Efforts to improve student manners by implementing hadith-based group guidance" aims to find out how to improve student manners by implementing hadith-based group guidance. A qualitative approach and descriptive research methods were used by researchers in research with a total of 10 students from the BPI (Islamic Guidance Guidance) study program. Apart from interview techniques, researchers used documentation techniques and observation techniques to collect data. The data analysis used is qualitative descriptive data analysis. This research obtained results namely (a) efforts to improve student manners were carried out through hadith-based group guidance with several processes or stages such as (1) formation, (2) transition, (3) activities, (4) conclusion, and (5) closing , and (b) student politeness has improved both in behavioral and language aspects.